Niche Differentiation of Sulfate- and Iron-Dependent Anaerobic Methane Oxidation and Methylotrophic Methanogenesis in Deep Sea Methane Seeps - Li, Haizhou; Yang, Qunhui; Zhou, Huaiyang (Frontiers in Microbiology, 2020)
Methane seeps are widespread seafloor ecosystems shaped by complex physicochemical-biological interactions over geological timescales, and seep microbiomes play a vital role in global biogeochemical cycling of key elements on Earth. However, the mechanisms underlying the coexistence of methane-cycling microbial communities remain largely elusive. Here, high-resolution sediment incubation experiments revealed a cryptic methane cycle in the South China Sea(SCS) methane seep ecosystem, showing the coexistence of sulfate (SO42-)- or iron (Fe)- dependent anaerobic oxidation of methane (AOM) and methylotrophic methanogenesis. This previously unrecognized methane cycling is not discernible from geochemical profiles due to high net methane consumption. High-throughput sequencing and CARD-FISH results suggested that anaerobic methane-oxidizing archaea (ANME) -2 and -3 coupled to sulfate-reducing bacteria (SRB) carried out SO42--AOM, and alternative ANME-2 and -3 solely or coupled to iron-reducing bacteria (IRB) might be participate in Fe-AOM in sulfate-depleted environments. This finding suggested that ANME could alter AOM metabolic pathways according to geochemical changes. Furthermore, the majority of methylotrophic methanogens belonged to Methanimicrococcus, and hydrogenotrophic and acetoclastic methanogens were likely inhibited by sulfate or iron reducing respiration. Fe-AOM and methylotrophic methanogenesis are overlooked potential sources and sinks of methane in methane seep ecosystems, thus influencing methane budgets in the ocean and even the global carbon budget.